The Notary Public in Singapore - Steffanny Cristine (Jurnal Akta, 2021)
Singapore law, which has its root in English law, has now evolved into a distinctive jurisprudence. It continues to absorb and modify the common law as well as best practices from other mature legal systems. The common law system in Singapore bears material differences from some Asian countries which have imbibed the civil law tradition such as the legal profession. The common law is one important strand of Singapore politico legal fabric. Singapore has inherited the English common law tradition as a part of Anglo Saxon countries and thus enjoys the attendant benefits of stability, certainty and internationalization inherent in the British system. Singapore shares similar English common law roots with some neighbours, such as Malaysia, Brunei, India and Myanmar through the details of the application and implementation will differ according to each country’s specific needs and policies, same goes to the legal professional they are adopted.